Insertion/deletion polymorphism of the angiotensin-converting enzyme gene and the risk of hypertension among residents of two cities, South-South Nigeria (2014)
Background: Hypertension is a public health challenge due to its high prevalence, and is a major risk factor for cardiovascular diseases. This study was designed to determine the frequency of the I/D polymorphism of the angiotensin-converting enzyme gene and its association with hypertension in a sample population of Calabar and Uyo, South-South Nigeria. Materials and Methods: A population-based case control design consisting of total of 1224 participants, 612 each of patients and controls, were randomly recruited from hypertension clinics and the general population. The I/D polymorphism was investigated using polymerase chain reaction. Multiple regression and odds ratio (OR) was applied to test whether the ID genotypes were predictors of hypertension. Results: The I/D genotype frequencies were 73(12%), 262(43%) and 277(45%); 74(12%), 303(50%) and 235(38%) for the II, ID, DD genotype in patient and control groups, respectively. A higher frequency of the ID genotype was observed in controls of which 208(61%) were females. By multiple regression analysis, age was a predictor for SBP in patients, r = 0.596, and DBP in controls, r = 0.555. Gender, Body mass index, I/D genotypes were not significant predictors for hypertension but the I/D polymorpism was associated with an increased risk for hypertension with an OR of 1.15 95%CI (0.924-1.456). Conclusion: The I/D polymorphism of the angiotensin-converting enzyme gene was a risk factor for hypertension in the sample population of Calabar and Uyo. This research will form baseline information for subsequent molecular studies in this population.